5PSQ-131 Parenteral nutrition in acute pancreatitis: a review of appropriateness. (23rd March 2022) - Sebastián, C; Garreta, G; Meca, N; Salazar, F; Rodrigo, M; Nicolas-Pico, J
Abstract : Background and importance: According to nutritional recommendations in patients with pancreatitis, adequate nutrition from the beginning has a high impact on the pathology, since these are patients at risk of malnutrition. Aim and objectives: To review the adequacy of individualised total parenteral nutrition (TPN) in patients admitted with a diagnosis of acute (AP) or exacerbated (rPAP) pancreatitis. Material and methods: Retrospective observational study including patients admitted from January 2020 to September 2021, all diagnosed with AP or rPAP. The following variables were collected from the HCIS clinical history and Kabisoft TPN prescription program: age, sex, height, weight, diagnosis, initial TPN composition (lipids, carbohydrates, proteins), days from admission to initiation of TPN and reason for initiation. Results: A sample of 53 patients was obtained, 33 men, of whom 42 were diagnosed with BP (79.25%) and 10 with rPAP (18.87%) on admission. The mean number of days to initiation of TPN was 3.30 (±1.90) days. The majority of patients, 48 of the total, started TPN due to contraindications to an oral diet. Only 10 had a lipid intake ≥0.8 g/kg/day; the rest had less, with a mean of 0.6 (±0.23) g/kg/day. Protein intake was 1.1 (±0.23) and carbohydrates 2.8 (±0.55) g/kg/day. Lipids accounted on average for 26.2% (±7.31) of the average caloric intake (ACT), protein 21.4% (±3.25) and carbohydrates 52.4% (±5.82). Twenty-eight of the TPNs had an ACT lower than the calculated requirements. The average non-protein kcal/g nitrogen (kcalNP/gN) was 94.8 (±19.20) and non-protein kcal/kg on average was 16.8 (±3.84). Conclusion and relevance: In line with the European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines, protein, carbohydrate and lipid intake, and non-protein kcal/kg, were lower than recommended. Total TPN kilocalories were also lower than the calculated requirements of the patients. This may be due to the fact that energy needs change according to AP severity and stage. Also, there is risk of malnutrition and, consequently, refeeding syndrome. However, the kcalNP/gN ratio was adequate, ensuring that protein was used for tissue formation. The caloric intake of carbohydrates with respect to ACT was adequate, being between the recommended 50%–70%. More clinical nutrition interventions will be necessary, always integrated by a multidisciplinary team. References and/or acknowledgements: 1. ESPEN guideline on clinical nutrition in acute and chronic pancreatitis. Clin Nutr 2020;39 :612–631. 2. ESPEN guidelines on parenteral nutrition: pancreas. Clin Nutr 2009;28 :428–435. Conflict of interest: No conflict of interest